An assessment of the core capacities of the Senegalese health system to deliver Universal Health Coverage - Elisabeth Paul; Youssoupha Ndiaye; Farba L. Sall; Fabienne Fecher; Denis Porignon (Elsevier, 2020)
Senegal is firmly committed to the objective of universal health coverage (UHC). Various initiatives have been launched over the past decade to protect the Senegalese population against health hazards, but these initiatives are so far fragmented. UHC cannot be achieved without health system strengthening (HSS). Here we assess the core capacities of the Senegalese health systems to deliver UHC, and identify requirements for HSS in order to implement and facilitate progress towards UHC. Based on a critical review of existing data and documents, complemented by the authors' experience in supporting UHC policy making and implementation, we evaluate the main foundational and institutional bottlenecks relative to the six health system building blocks, together with an analysis of the demand-side of the health system, which facilitate or hamper progress towards UHC. Despite the fact that many institutions are now in place to deliver UHC, important weaknesses limit progress along the two dimensions of UHC. Substantial disparities characterise resource allocation in the health sector, and health risk protection schemes are highly fragmented. This spreads down to the rest of the health system including service delivery and consequently, impacts on health outcomes. These constraints are acknowledged by the authorities, solutions have been proposed, but these necessitate strong political will. Moreover, progress towards UHC is constrained by the difficulty to act on social determinants of health and a lack of fiscal space.